On a new species of coral-symbiont crab of the genus Cymo de Haan, 1833 (Crustacea: Decapoda: Brachyura: Xanthidae), from the South China Sea - Ho, P.-H.; Ng, Peter K.l. (Zootaxa, 2005)
A new species of obligate coral symbiont crab of the genus Cymo de Haan, 1833 (Brachyura: Xanthidae) is described from the Indonesian Anambas Islands in the South China Sea. The species is allied to C. deplanatus A. Milne-Edwards, 1873, but is easily distinguished by a suite of carapace, cheliped, male abdominal and gonopod characters. A revised key to the genus Cymo is presented.